2019
DOI: 10.1111/acel.13078
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of REV‐ERBs stimulates microglial amyloid‐beta clearance and reduces amyloid plaque deposition in the 5XFAD mouse model of Alzheimer’s disease

Abstract: A promising new therapeutic target for the treatment of Alzheimer's disease (AD) is the circadian system. Although patients with AD are known to have abnormal circadian rhythms and suffer sleep disturbances, the role of the molecular clock in regulating amyloid‐beta (Aβ) pathology is still poorly understood. Here, we explored how the circadian repressors REV‐ERBα and β affected Aβ clearance in mouse microglia. We discovered that, at Circadian time 4 (CT4), microglia expressed higher levels of the master clock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 48 publications
4
80
1
4
Order By: Relevance
“…Mechanistically, a CHiPseq experiment revealed that REV-ERBα binds the promoter of NF-κB target genes linked to the inflammatory response such as Traf2 and NF-κB inhibitor beta (Nfkbib), an inhibitor of NF-κB nuclear translocation. A follow-up study in a 5XFAD mouse model of AD revealed that inhibition of REV-ERBα pharmacologically or through genetic knockdown pushed microglia towards a phagocytic phenotype as measured by an increase in Aβ clearance and a decrease in plaque deposition [257].…”
Section: Circadian Rhythm Regulates Microglia Pro-inflammatory Responsementioning
confidence: 99%
“…Mechanistically, a CHiPseq experiment revealed that REV-ERBα binds the promoter of NF-κB target genes linked to the inflammatory response such as Traf2 and NF-κB inhibitor beta (Nfkbib), an inhibitor of NF-κB nuclear translocation. A follow-up study in a 5XFAD mouse model of AD revealed that inhibition of REV-ERBα pharmacologically or through genetic knockdown pushed microglia towards a phagocytic phenotype as measured by an increase in Aβ clearance and a decrease in plaque deposition [257].…”
Section: Circadian Rhythm Regulates Microglia Pro-inflammatory Responsementioning
confidence: 99%
“…Wu et al (2018) showed a slight phase delay and decreased expression of Per1/2 in the SCN of 3xTG mice, while Ma et al (2016) showed altered rhythms in hippocampal Bace2 and Apoe mRNA. Other studies in AD models have examined clock gene expression at one or two time points throughout the circadian cycle, usually early morning and early evening, in some case showing a loss of variation in AD mice (Duncan et al, 2012;Bellanti et al, 2017;Stevanovic et al, 2017;Lee et al, 2020). While these can be used to make general conclusions, it is difficult to interpret if clock genes are changing amplitude, or if there is just a difference in phase of expression of that particular gene.…”
Section: Impact Of Ad Pathology On Clock Gene Expressionmentioning
confidence: 99%
“…Previous work from our group shows that deletion of BMAL1 or its downstream target REV-ERBα causes neuroinflammation and impaired brain functional connectivity ( Griffin et al, 2019 ; Musiek et al, 2013 ). Diminished BMAL1 and REV-ERBα expression have also been described in mouse models of Alzheimer’s disease (AD)( Lee et al, 2020 ; Stevanovic et al, 2017 ). In AD, memory-associated, synapse-rich regions such as the hippocampus are affected early in the disease course ( Braak et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%